ANALISIS PENERAPAN KOMPENSASI, LINGKUNGAN, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DITOKO BAHAN BANGUNAN SAHABAT NGANJUK - ADILIA PUTRI, SELVI (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The goal of this study is to determine whether (1) compensation has a substantial impact on the performance of Nganjuk Sahabat Building Materials Store employees. (2) The environment has a substantial impact on the performance of Nganjuk Sahabat Building Materials Store personnel. (3) Workload has a substantial impact on the performance of Nganjuk Sahabat Building Materials Store personnel. (4) Compensation, atmosphere, and workload all have a substantial impact on the performance of Nganjuk Sahabat Building Materials Store personnel. Employees of the Sahabat of Nganjuk Building Materials Store were the subjects of this study. The total sampling approach was used in this investigation, which yielded 40 respondents. Multiple linear regression become used to have a look at the facts the use of the SPSS Version 26 tool. (1) Partial remuneration has a substantial effect on the performance of employees at the Nganjuk Sahabat Building Materials Store, according to the findings of this study. (2) The environment has a substantial impact on the performance of Nganjuk Sahabat Building Materials Store personnel. (3) Workload has a substantial impact on the performance of Nganjuk Sahabat Building Materials Store personnel. (4) Compensation, atmosphere, and workload all have a substantial impact on the performance of Nganjuk Sahabat Building Materials Store personnel.